7 Prevalence and Severity of Obstructive Sleep Apnea in Men with Polycythemia on Testosterone Therapy. Issue 1 (1st April 2022) - Salter, C; Flores, JMF; Schofield, E; Tan, M; Mulhall, J
ABSTRACT: Introduction: Polycythemia is independently associated with both testosterone therapy (TTH) and obstructive sleep apnea (OSA). Objective: The purpose of this study was to evaluate the prevalence and severity of OSA in men who experience polycythemia while on TTH. Methods: Study population included men who had polycythemia [hematocrit (HCT) >50%] while on TTH for TD, with total and free T levels within the normal range. Men completed screening questionnaires for OSA and daytime sleepiness, respectively: STOP-BANG (SB, range 0-8) and the Epworth Sleepiness Scale (ESS, range 0-24). Men whose scores demonstrated intermediate to high risk of OSA proceeded to a diagnostic sleep study which recorded the following parameters: apnea hypoxia index (AHI, normal <5 events/h), total duration SpO2 saturation <88% and SpO2 nadir. Descriptive statistics are presented. Results: 73 men had a mean age of 60±11.5 years. Mean HCT pre-TTH and on TTH were 45±3% and 52±1.5%, respectively, for a mean increase of 6.6±3.6%. Mean on-treatment total T level 686±285 ng/dL. Median STOP-BANG score was 4 (IQR 3-5), median ESS score was 5 (IQR 3-9). 63% of patients screened positive for OSA on questionnaires. 81% of sleep studies confirmed OSA; mean AHI of the group was 15.4±13.2 events/hour (range 1.6-54.6 events/hour). 36% of men had AHI≥15 events/hour and 14% ≥30 AHI events/hour. Mean SpO2 nadir was 83±5% (range 69%-93%). 67% of men with OSA had an oxygen nadir in the 80s, 19% in the 70s and 3% in the 60s. Total duration of hypoxia (SpO2 ≤88%) was 32±50 minutes (range 0.1-202 minutes), 46% of men having hypoxia <10 minutes, 8% 10-20 minutes, 19% 70-150 minutes. Conclusions: Men on TTH who are eugonadal that experience polycythemia have high rates of OSA. 80% of the patients undergoing sleep study had OSA. These data suggest that men with polycythemia on TTH should be screened for OSA. Disclosure: No